Notes to Philosophy 167: Class 6 -- Galileo's Two New Sciences: Local Natural Motion -- Complete. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Local Motion Versus Celestial Motion: The Problem -- "The Third Day": Some Conceptual Obstacles -- "The Third Day": Evidential Difficulties -- Galileo's Contribution to Science: Some Issues -- Select sources.; Section: Class 6, Complete.